Efficient detection of Cu2+, Fe3+ and Cr2O72− in aqueous solution using two new Co(II) luminescent metal-organic frameworks. (1st March 2023) - Ru, Jing; Wang, Ying-Xue; Shi, Yi-Xuan; Guo, Qiang; Wang, Yan-Lan; Ma, Chun-Lin
Graphical abstract: In this work, two new three-dimensional Co(II) metal-organic frameworks (MOFs), [Co2 (TFBA)(4, 4′-bpy)H2 O]·5DMF·7H2 On (CoMOF-1 ) and [Co2 (TFBA)(bpen)H2 O] ·6DMF·6H2 O n (CoMOF-2 ) (H3 TFBA = tris(3′-F-4′-carb oxybiphenyl)amine, 4, 4′-bpy = 4, 4′-bipyridine, bpen = trans -1, 2-bis(4-pyridyl)ethene) were constructed by a solvothermal method. Both CoMOF-1 and CoMOF-2 displayed similar 3D frameworks with the 2, 3, 4, 6-c net topology based on dinuclear [Co2 O8 ] units. The powder X-ray diffraction (PXRD) results and thermogravimetric analysis (TGA) proved that CoMOF-1 and CoMOF-2 have good structural and thermal stability. As we expected, the luminescence sensing investigations demonstrated that CoMOF-1 and CoMOF-2 could be considered as promising luminescent sensors toward Cu 2+, Fe 3+ and Cr2 O7 2− ions via a quenching effect, with high sensitivity and good reusability. Additionally, the possible luminescent quenching reasons were systematically studied by UV spectroscopy, X-ray photoelectron spectroscopy (XPS), IR spectra and PXRD patterns. Abstract: In this work, two new three-dimensional Co(II) metal-organic frameworks (MOFs), [Co2 (TFBA)(4, 4′-bpy)H2 O]·5DMF·7H2 On (CoMOF-1 ) and [Co2 (TFBA)(bpen)H2 O] ·6DMF·6H2 O n (CoMOF-2 ) (H3 TFBA = tris(3′-F-4′-carb oxybiphenyl)amine, 4, 4′-bpy = 4, 4′-bipyridine, bpen = trans -1, 2-bis(4-pyridyl)ethene) were constructed by a solvothermal method. Both CoMOF-1 and CoMOF-2 displayed similar 3D frameworks with the 2, 3, 4, 6-c net topology based on dinuclear [Co2 O8 ] units. The powder X-ray diffraction (PXRD) results and thermogravimetric analysis (TGA) proved that CoMOF-1 and CoMOF-2 have good structural and thermal stability. As we expected, the luminescence sensing investigations demonstrated that CoMOF-1 and CoMOF-2 could be considered as promising luminescent sensors toward Cu 2+, Fe 3+ and Cr2 O7 2− ions via a quenching effect, with high sensitivity and good reusability. Additionally, the possible luminescent quenching reasons were systematically studied by UV spectroscopy, X-ray photoelectron spectroscopy (XPS), IR spectra and PXRD patterns.